Pedagogy Matters, Too: The Impact of Adapting Teaching Approaches to Formal Learning Environments on Student Learning. (March 2014) - Brooks, D. Christopher; Solheim, Catherine A.
Abstract : This chapter reveals how thoughtful course redesign that specifically addresses the physical environment of a learning space can significantly improve student learning.